Diversity of soil mites (Acari: Mesostigmata: Gamasina) in various deciduous forest ecosystems of Muntenia region (southern Romania) - Manu, Minodora (Biological Letters, 2014)
The main task of the research was to investigate the diversity of predatory soil mites (Gamasina) in 8 types of forest ecosystems: alder (Călugăreni, Clinceanca, Azuga Valley, Cumpătu), oak-hornbeam (Baloteşti, Băneasa), beech (Şotrile), and fir-beech (Lunca Mare) in Muntenia region. Taxonomical classification and statistical methods used in this study show similarities as well as differences between their predatory mite communities. In total, 467 mites of 57 gamasid species were identified, belonging to 28 genera and 12 families. Veigaia nemorensis, Prozercon fimbriatus, P. kochii, and P. traegardhi were most abundant. Geographical position, abiotic factors (soil type, slope angle, soil moisture content, pH) and biotic ones (vegetation structure: herbs, shrubs or trees) were related to differences in gamasid species composition between the investigated forest ecosystems.